Distribution, relative abundance, and developmental morphology of paralarval cephalopods in the Western North Atlantic Ocean - Vecchione, Michael; Roper, Clyde F. E.; Sweeney, Michael J.; Lu, C. C. (National Marine Fisheries Service, 2001)
Paralarval and juvenile cephalopods collected in plankton samples on 21 western North Atlantic cruises were identified and enumerated. The 3731 specimens were assigned to 44 generic and specific taxa. This paper describes their spatial and temporal distributions and their developmental morphology. The smallest paralarvae recognized for a number of species are identified and illustrated. The two most abundant and most frequently collected taxa were identifiable to species based on known systematic characters of young, as well as on distribution of the adults. These were the neritic squids Loligo pealeii and Illex illecebrosus collected north of Cape Hatteras, both valuable fishery resources. Other abundant taxa included two morphotypes of ommastrephids, at least five species of enoploteuthids, two species of onychoteuthids, and unidentified octopods. Most taxa were distributed widely both in time and in space, although some seasonal and mesoscale-spatial patterns were indicated. The taxa that appeared to have distinct seasonal distribution included most of the neritic species and, surprisingly, the young of the bathypelagic cranchiids. In eight seasonal cruises over the continental shelf of the middle U.S. Atlantic states, neritic taxa demonstrated approximately the same seasonal patterns during two consecutive years. Interannual differences in the oceanic taxa collected on the shelf were extreme. The highest abundance and diversity of planktonic cephalopods in the oceanic samples were consistently found in the vicinity of the Gulf Stream. Only eight of the oceanic taxa appeared to have limited areal distributions, compared with twelve taxa that were found throughout the western North Atlantic regions sampled in this study. Many taxa, however, were not collected frequently enough to describe seasonal or spatial patterns. Comparisons with published accounts of other cephalopod surveys indicate both strengths and weaknesses in various sampling techniques for capturing the young of oceanic cephalopods. ...